2007
DOI: 10.2320/matertrans.mi200715
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnetic Field and Deformation on Isothermal Martensitic Transformation in SUS304 and SUS304L Steels

Abstract: Effects of external fields, such as temperature, magnetic field, stress and combination of these fields have been examined on martensitic transformation of SUS304 and SUS304L austenitic stainless steels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…0 martensitic transformation proceeded by isothermal holding. 7,8) As far as the authors are aware, this was the first finding of isothermal successive ! " 0 !…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…0 martensitic transformation proceeded by isothermal holding. 7,8) As far as the authors are aware, this was the first finding of isothermal successive ! " 0 !…”
Section: Introductionmentioning
confidence: 97%
“…That is, f 0 ¼ M 0 ðT R Þ=M 0 0 ðT R Þ, where M 0 ðT R Þ and M 0 0 ðT R Þ are the spontaneous magnetization of the specimen and that of the 0 -phase, respectively, at T R . 8) Here, the magnetizations of -phase and " 0 -martensite are neglected because they are nonmagnetic. 9,10) The value of M 0 0 ðT R Þ is approximated to be the value at 0 K, M 0 0 ð0Þ, although it is a rough approximation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14] Recently, we found that the sensitized SUS304 stainless steel exhibits an isothermal martensitic transformation at cryogenic temperatures. 15,16) However, its time-temperature-transformation (TTT) diagram, which is one of the most important information for isothermal transformations, has not been constructed yet.…”
Section: Introductionmentioning
confidence: 99%